Diagnosis and Management of Achalasia in Children - I Gede Sugiana Karaeng; Rasyidah; Efriyan Imantika (Medula, 2019)
Achalasia is a rare neurogenic motility disorder, occurring in around 0.11 cases per in 100,000 children. Changes morphology of the ganglion in the myenteric plexus can be identified at the LES(Lower Esophageal Sphincter)level. Some researchers have shown a decrease in vasoactive peptide (IVP) immunoreactivity in nerve fibers. In the pediatric, most achalasia was reported during adolescence, more often in boys. The combination of problems named (aperistaltic, LES hypertension, and lack of LES relaxation) results in patients experiencing symptoms of progressive dysphagia, weight loss, and regurgitation. A chest x-ray of a child with achalasia may show a dilated esophagus and air-fluid level. The use of barium swallow will show the esophagus is winding and wide, yet sometimes narrow on the cardia part like a bird's beak. Diagnosis is confirmed by esophageal manometry. Esophageal endoscopic examination is very important to get rid of stricture. Treatment modalities have developed over the past few decades from balloon dilatation and injection of botulinum toxin to laparoscopic Heller myotomy and endoscopic myotomy. Most data on achalasia management is extrapolated to children from adult experience. This article describes an understanding of pathogenesis and discusses newer therapeutic techniques and controversies in management.